Pyrolysis kinetics of pine sawdust in a fixed bed - Yilgin, Melek; Pehlivan, Dursun; Aydoğmuş, Ercan; Duranay, Neslihan (International University of Sarajevo, 2017)
Currently worldwide studies are being done on the utilisation of lignocellulosic materials or biomasses as substitutes of fossil fuels to afford energy needs of today's world. Pyrolysis is one of the most promising techniques for apprising biomass into economically viable renewable fuels. In this work, pyrolysis behaviour of pine sawdust was investigated experimentally in a fixed bed system with mass measurements under nitrogen as sweeping gas. The main objective was to interpret mass loss of pine sawdust during pyrolysis at varied heating rates and to estimate kinetic constants using the best mathematical model among the popular solid phase decomposition models. Regression tests are separately applied to conversion data for 473 - 593 K and 593 - 773 K temperature ranges, corresponding respectively decomposition of hemicelluloses and cellulose, and cellulose and lignin. The quality of fit increased with heating rate and none of the proposed models had any superiority to others. The results implied that volatiles evolution during pyrolysis was increasingly controlled chemically with heating rate.
Keywords: Fixed bed; Kinetics; Pine wood; Pyrolysis